Recent Applications of Bioinformatics in Target Identification and Drug Discovery for Alzheimer’s Disease - Singh S.K.; Kumar A.; Singh R.B.; Ghosh P.; Bajad N.G. (My University, 2025)
Alzheimer's disease (AD) is a complex multifactorial neurodegenerative disease charac-terized by progressive memory loss. The main pathological features of the disease are extracellular deposition of amyloid β (Aβ) plaques and intracellular neurofibrillary tangles composed of hyper-phosphorylated tau protein. Understanding factors contributing to AD progression, the number of molecular signatures, and the development of therapeutic agents played a significant role in the discovery of disease-modifying drugs to treat the disease. Bioinformatics has established its signifi-cance in many areas of biology. The role of bioinformatics in drug discovery, is emerging significantly and will continue to evolve. In recent years, different bioinformatics methodologies, viz. protein signaling pathway, molecular signature differences between different classes of drugs, inter-acting profiles of drugs and their potential therapeutic mechanisms, have been applied to identify potential therapeutic targets of AD. Bioinformatics tools were also found to contribute to the discovery of novel drugs, omics-based biomarkers, and drug repurposing for AD. The review aims to explore the applications of various advanced bioinformatics tools in the identification of targets, biomarkers, pathways, and potential therapeutics for the treatment of the disease. © 2022 Bentham Science Publishers.